Scaling Strategy for Smart Nkunganire System (SNS) in Rwanda: Increasing the Incomes of Smallholder Farmers between 2025 to 2028 - Sartas, M.; Mudereri, B.T.; Kihoro, Esther; Senge, M.; Rabourn, T.R.; Ogunsanmi, T.; Uzamushaka, S.; Kangethe, E.; Muzata, B.S.; Guchu, W. (2025)
The Smart Nkunganire System (SNS), a digital platform developed through a public-private partnership, has revolutionised Rwanda's input supply chain since its launch in 2017. It has registered over 2.4 million farmers, facilitated the distribution of over 131,380 metric tons of agro-inputs, and managed transactions exceeding 85 billion RWF annually. This strategy outlines a plan to scale the SNS fertiliser recommendation module between 2025 and 2028, aiming to significantly improve the incomes of smallholder farmers while contributing to Rwanda's food security and economic growth.